Study of the 33Cl spectroscopic factors via the 32S(3He, d)33Cl one-proton transfer reaction. (20th April 2021) - Lombardo, I; Dell'Aquila, D; Cinausero, M; Gasques, L R; Vigilante, M; Zagatto, V A B; Barlini, S; Bolzonella, R; Bruno, M; Buccola, A; Camaiani, A; Carturan, S M; et al.
Abstract: In this paper we discuss new experimental data on the one-proton transfer reaction 32 S( 3 He, d) 33 Cl * at 9.68 MeV bombarding energy. An enriched 32 S target and a high-granularity hodoscope were used to obtain data for proton transfer reactions to bound and unbound states in 33 Cl. Angular distributions were interpreted by means of finite-range DWBA and coupled-channel calculations. The obtained spectroscopic factors have been compared with previous results reported in the literature and with shell model calculations.